Transcriptome Analysis Provides Insights Into the Adaptive Responses to Hypoxia of a Schizothoracine Fish (Gymnocypris eckloni) - Qi, Delin; Chao, Yan; Wu, Rongrong; Xia, Mingzhe; Chen, Qichang; Zheng, Zhiqin (Frontiers in Physiology, 2018)
The schizothoracine fish endemic to the Qinghai-Tibetan Plateau are comparatively well adapted to aquatic environments with low oxygen partial pressures. However, few studies have used transcriptomic profiling to investigate the adaptive responses of schizothoracine fish tissues to hypoxic stress. This study compared the transcriptomes of Gymnocypris eckloni subjected to 72 h of hypoxia (DO = 3.0 ± 0.1 mg/L) to those of G. eckloni under normoxia (DO = 8.4 ± 0.1 mg/L). To identify the potential genes and pathways activated in response to hypoxic stress, we collected muscle, liver, brain, heart, and blood samples from normoxic and hypoxic fish for RNA-seq analysis. We annotated 337,481 genes. Of these, 462 were differentially expressed in the hypoxic fish as compared to the normoxic fish. Under hypoxia, the transcriptomic profiles of the tissues differed, with muscle the most strongly affected by hypoxia. Our data indicated that G. eckloni underwent adaptive changes in gene expression in response to hypoxia. Several strategies used by G. eckloni to cope with hypoxia were similar to those used by other fish, including a switch from aerobic oxidation to anaerobic glycolysis and the suppression of major energy-requiring processes. However, G. eckloni used an additional distinct strategy to survive hypoxic environments: a strengthening of the antioxidant system and minimization of ischemic injury. Here, we identified several pathways and related genes involved in the hypoxic response of the schizothoracine fish. This study provides insights into the mechanisms used by schizothoracine fish to adapt to hypoxic environments.